PascalÊ¾s Pensées and BaudelaireÊ¾s Les fleurs du mal : a study of the parallels and development of the theme of ÊºennuiÊº - Hammond, Nicholas Gascoigne (Rhodes University, Faculty of Humanities, School of Languages, 1987)
From Introduction: Upon first reading the writings of both Pascal and Baudelaire, one cannot help being struck by a sensation of awe at the penetrating insight into the human condition possessed by both writers. A further exploration of the realms of Pascalian and Baudelairian thought considerably strengthens this initial reaction into a recognition that both authors were men of equal moral and spiritual intensity. Despite their outward differences, both sought to attain a deep understanding of human nature, but without attempting to offer any excuses on behalf of man. Furthermore, the two writers employ an identical term to describe the condition of humanity: "ennui". Although the word exists in the writings of contemporaries of both Pascal and Baudelaire, no other author makes such full, unique and significant use of ennui. As this thesis will hopefully prove, Baudelaire was indeed directly and positively influenced by Pascal. However, it is not our intention to concentrate upon such an influence; rather, we wish to indicate the parallels and development of the theme of ennui, so central to each man's outlook, in their respective writings. Evidently, it would be beyond the boundaries of this thesis if we were to try to analyse closely the entire creative output of Pascal and Baudelaire; and so, although their other works will act as points of reference, the two books which are generally regarded as their masterpieces will be used as the basis of the unfinished Christian "Apologie" which was projected by Pascal, now known as the Pensées (1670), and Baudelaire's Les Fleurs du Mal (1857 and 1861)
Keywords: Pascal, Blaise, 1623-1662 -- Criticism and interpretation; Pascal, Blaise, 1623-1662 -- Pensées; Baudelaire, Charles, 1821-1867 -- Criticism and interpretation; Baudelaire, Charles, 1821-1867 -- Fleurs du mal